Micro-scale study on fatigue behavior of fiber reinforced concrete - Lim, Xin Ni (2015)
Fatigue performance of engineered cementitious composites (ECC), a unique group of ductile fiber reinforced concrete (FRC) has been reported in various literatures. Fatigue-induced premature failure of ECC composites was observed in macro-scale experiments. Specifically, the premature failure lowers strain capacity and number of cracks formed. In order to enhance the structural performance of ECC composites’ under fatigue loading, it is essential to improve the fiber-bridging fatigue performance through micromechanics-based tailoring (fiber, fiber-matrix and matrix properties). However, it was revealed that the in-situ strength of embedded fiber is remarkably reduced by fatigue loading and the tensile pullout stiffness of embedded fiber is increased by the fatigue-hardening effect. Both changes would produce negative impact to fiber-bridging properties. Hence, in this research, effects of fiber surface oil-treatment on fatigue and post-fatigue performance of single embedded polyvinyl alcohol (PVA) fiber were studied. The experimental results indicate that, oil-treatment mitigates the deterioration of fatigue in-situ fiber strength and reduces fatigue-hardening effect. It is expected that in future, with the results discovered in this research incorporated into existing micromechanics-based model for ECC design, ECC structural stress, strain capacity and service life can be further improved.